Development of Gadung Tuber Processing E-Module Based on Discovery Learning at SMAN 1 Seteluk, West Sumbawa Regency - Juliana, Juliana; Rahmawati, Fitri; Ashari, Ari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to determine the feasibility of an e-module for processing gadung tubers (dioscorea hispida) based on a discovery learning model and to determine the readability test of developing an e-module for processing gadung tubers (dioscorea hispida) based on a discovery learning model by students in class X-6 of SMA Negeri 1 Seteluk. This e-module was developed using a 4D development model by Thiagarajan, but this research was limited to the 3D stage. The 3D stages are Definition, planning (Design) and development (Develop). Based on the research results, it shows that the e-module was declared valid according to the validation results of 63.75%, the readability test by teachers was 78.75% and the readability test by students was 76.13%. Thus, e-modules are suitable for implementation in the learning process by teachers in the future.